Analyzing Social Functions in English Textbook Dialogs: A Study of Bahasa Inggris Kelas X - Yoannes Yuka Krisdianata (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study investigates the representation of social functions of language in dialogs presented in the government-issued 2017 edition English textbook Bahasa Inggris Kelas X. Grounded in Halliday’s functional linguistics and the content mapping framework of Widiati et al. (2017), this study aims to identify the social functions of language introduced in the dialogs of the English textbook Bahasa Inggris SMA/MA/SMK/MAK Kelas X (2017 revised edition). Using a qualitative content analysis approach, sixteen dialogs across six chapters were examined and categorized based on their communicative purposes. The analysis revealed four dominant social functions: (1) introducing and mentioning identity, (2) expressing congratulations and compliments, (3) stating and asking about intentions, and (4) retelling past events in chronological order. The findings indicate that while the textbook provides a foundation for developing interpersonal communication, the coverage of social functions is limited, with an emphasis on congratulatory and complimentary expressions. This suggests a need for more balanced representation of diverse communicative purposes to better prepare learners for authentic interaction. The study highlights implications for textbook authors, teachers, and policymakers, recommending further integration of varied social functions and supplementary classroom activities to address the identified gaps.